Wavelength conversion of SCM signals using semiconductor optical amplifiers: theory, experiments, and applications - Capmany, J.; Sales, S.; Pastor, D.; Martinez, A.; Ortega, B. (Journal of lightwave technology, 2003)
In this paper, we deal with the subject of cross-gain modulation (XGM) and cross-phase modulation (XPM) semiconductor optical amplifier-based wavelength conversion of optical channels carrying subcarrier multiplexing signals in a comprehensive way. The equations and models that describe the conversion process and the resulting harmonic and intermodulation distortions are obtained showing the superior performance of XPM over XGM in terms of secondand third-order distortion and contrast ratio. Experimental results for XGM-based wavelength conversion that confirm the results predicted by our theoretical models are presented, and finally, we consider the specific application of wavelength conversion of optical channels carrying full frequency plans such as that of cable television applications.